Changes of high order aberrations after photorefractive keratectomy (PRK) and FemtoLASIK - N. V. Khodzhabekyan; A. T. Khandzhyan; E. P. Tarutta; S. G. Harutyunyan; M. D. Sengaeva (Российский офтальмологический журнал)
Purpose: a comparative study of corneal and total wavefront aberration changes after traditional PRK and FemtoLASIK.Material and methods. Corneal and total wavefront aberrations were studied on OPD-Scan III aberrometer (Nidek) in 63 patients (126 eyes) with moderate and high myopia before and after FemtoLASIK (Ziemer + Nidek-Quest, Japan) (44 patients, 88 eyes) and PRK (Nidek-Quest, Japan) (19 patients, 38 eyes). Spherical aberration (SA) was considered as the sum Z4 + Z8 + Z12.Results. The corneal asphericity coefficient Q changed to positive values after both types of intervention. Corneal RMS HOA increased in both Femto and PRK groups. Corneal Tilt 1 increased after FemtoLASIK and moved to negative values after PRK, corneal tilt 2 moved to negative values after Femto and to positive values after PRK. The vertical trefoil showed no significant change in the Femto group and dropped in the PRK group. The vertical and horizontal coma (coma 7, coma 8) changed synchronously. Corneal SA increased after Femtolasic, and became negative after PRK. The total aberrations showed a lesser change and the changes were not synchronized with the corneal ones: in particular, the RMS HOA fell from 0.28 ± 0.05 to 0.19 ± 0.05 in the Femto group, while the corneal RMS increased significantly. In the PRK group, the corneal RMS HOA showed some increase, but it was much less than corneal RMS: from 0.25 ± 0.07 to 0.62 ± 0.02 μm. The total SA increased from 0.11±0.03 to 0.27±0.02 in the Femto group and showed an insignificant drop from 0.09±0.03 to 0.03 ± 0.01, while remaining positive in the PRK group.Conclusions. The changes of the wavefront after FemtoLASIK and PRK are both significant and different. The revealed differences in the changes of corneal aberrations correspond to different profiles of the anterior surface of the cornea formed after FemtoLASIC and PRK. The internal optics of the eye partially compensates the corneal aberrations induced by excimer laser surgery.